Home and community-based care for persons living with HIV/AIDS and AIDS in Thailand : lessons learned and future prospects - Bhassorn Limanonda (Chulalongkorn University, 2006)
Background -- Objectives and scope of the paper -- The expected outcome -- Home and community-based care: basic concept and definition -- HIV/AIDS epidemic: national situation and responses -- HIV/AIDS epidemic: regional situation -- Home and community-based care system: regional strategies development -- Key mechanisms to sustain home and community-based care system -- Conclusion: lessons learned and future prospects -- Issuses that need to be reconsidered